2009
DOI: 10.1080/10413200902785811
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disguise on Novice and Expert Tennis Players’ Anticipation Ability

Abstract: Skilled performers interpret cues in the preparatory movements of their opponents to anticipate future events in many sports. Little work has tested whether these cues can be disguised. Using a temporal occlusion paradigm, this paper examines the effect of disguise on an Australian sample of expert (16 male, 2 female, age M = 24.67, SD = 9.47 years) and novice players' (24 male, 38 female, age M = 22.26, SD = 5.24 years) anticipation of tennis ground strokes. Analysis of variance (ANOVA) showed that expert ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 5 publications
7
57
0
Order By: Relevance
“…Recently, Schorer, Baker, Fath, and Jaitner (2007) demonstrated that the functional variability in movement coordination increases when executing deceptive actions. Moreover, it is currently unknown how the deceptive and nondeceptive actions of an opponent affect athletes' gaze behaviors, and researchers examining the effect of deception on perceptual expertise have thus far reported unequivocal findings (for contrasting results, see Jackson et al, 2006;Rowe et al, 2009). An examination of the effects of penalty taker deceptive intent and goalkeeping performance is beyond the scope of the present study.…”
Section: Measurement Of Gaze Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Schorer, Baker, Fath, and Jaitner (2007) demonstrated that the functional variability in movement coordination increases when executing deceptive actions. Moreover, it is currently unknown how the deceptive and nondeceptive actions of an opponent affect athletes' gaze behaviors, and researchers examining the effect of deception on perceptual expertise have thus far reported unequivocal findings (for contrasting results, see Jackson et al, 2006;Rowe et al, 2009). An examination of the effects of penalty taker deceptive intent and goalkeeping performance is beyond the scope of the present study.…”
Section: Measurement Of Gaze Behaviorsmentioning
confidence: 99%
“…For example, in three recently published perceptual expertise studies, two-dimensional video tasks were utilized, with participant responses measured with either a keypress or a written judgment (Cañal-Bruland & Schmidt, 2009;Rowe, Horswill, Kronvall-Parkinson, Poulter, & McKenna, 2009;Sebanz & Shiffrar, 2009). Furthermore, an overview of methodological failings of the perceptual expertise literature with recommendations for future studies was recently provided by van der Kamp et al (2008).…”
mentioning
confidence: 99%
“…Additional studies conducted with this approach in mind have also appeared, with the aim to analyze this facet in a scientific light. An example of this can be the growing number of reports on such topics as situational awareness in tennis [17] or the ability to disguise one's shot strategy or the anticipation of an opponent's moves [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for superior performance of expert athletes in deception tasks has been provided in a number of previous studies, using the expert-novice approach. For example, domain-specific expertise enables athletes to better anticipate the direction of penalty kicks in soccer (Smeeton & Williams, 2012) and the direction of ground strokes in tennis (Rowe, Horswill, Kronvall-Parkinson, Poulter, & McKenna, 2009), to better predict a change of running direction of a rugby player with and without deceptive movement (Jackson, Warren, & Abernethy, 2006), and to recognize whether a team handball player throws or fakes a throw at the handball penalty shot (Cañal-Bruland & Schmidt, 2009;Cañal-Bruland, van der Kamp, & van Kesteren, 2010) or whether a basketball player passes the ball or fakes a pass to the teammate (Sebanz & Shiffrar, 2009). …”
Section: Introductionmentioning
confidence: 99%